2016
DOI: 10.1002/cmdc.201500594
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Highly Active Peroxisome Proliferator‐Activated Receptor (PPAR) β/δ Inverse Agonists with Prolonged Cellular Activity

Abstract: Based on 3-(((4-(hexylamino)-2-methoxyphenyl)amino)sulfonyl)-2-thiophenecarboxylic acid methyl ester (ST247, compound 2), a recently described peroxisome proliferator-activated receptor (PPAR)β/δ-selective inverse agonist, we designed and synthesized a series of structurally related ligands. The structural modifications presented herein ultimately resulted in a series of ligands that display increased cellular activity relative to 2. Moreover, with methyl 3-(N-(2-(2-ethoxyethoxy)-4-(hexylamino)phenyl)sulfamoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Some of the reported antagonistic ligands display inverse agonism in that they cause the PPAR-mediated transcription to fall below basal levels in a given model system or assay [ 91 , 94 , 95 , 97 , 103 ]. In similarity to other reported PPAR inverse agonists [ 104 106 ], the observed subbasal transcription levels are likely reflected in the tendency of such ligands to strengthen the interactions of the PPARs with corepressor proteins, such as NCoR and SMRT, compared to those of the apo-PPARs [ 85 , 88 , 93 , 103 106 ].…”
Section: Classical Ppar Agonism Antagonism and Beyondsupporting
confidence: 81%
“…Some of the reported antagonistic ligands display inverse agonism in that they cause the PPAR-mediated transcription to fall below basal levels in a given model system or assay [ 91 , 94 , 95 , 97 , 103 ]. In similarity to other reported PPAR inverse agonists [ 104 106 ], the observed subbasal transcription levels are likely reflected in the tendency of such ligands to strengthen the interactions of the PPARs with corepressor proteins, such as NCoR and SMRT, compared to those of the apo-PPARs [ 85 , 88 , 93 , 103 106 ].…”
Section: Classical Ppar Agonism Antagonism and Beyondsupporting
confidence: 81%
“… 34 , 35 The function of EFABP is to enhance the transcriptional activity of the nuclear receptors PPARβ/δ and promote cell migration, proliferation, and survival. 36 38 EFABP is overexpressed in many human cancers, including prostate cancer, 39 , 40 esophageal squamous cell carcinoma, 41 , 42 and breast cancer. 43 , 44 Previous studies have found that EFABP may play an important role in liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PT-S264 is an inverse PPARβ/δ agonist with improved repressive properties and stability (17). We first tested whether it affects initiation complex formation like the previously used inverse agonist ST247 (36), which reduces RNAPII binding to the ANGPTL4 promoter (4).…”
Section: Pparβ/δ Inverse Agonists Interfere With Formation Of An Initmentioning
confidence: 99%
“…Several fatty acids and their derivatives act as endogenous PPARβ/δ agonists (12,13,14,15). Agonistic ligands cause dissociation of corepressors from the nuclear receptor at ligandregulated target genes, while synthetic inverse agonists recently developed in our group lead to enhanced corepressor recruitment (4,7,16,17). Basal repression of ANGPTL4 and augmented repression in the presence of inverse agonists are largely insensitive to trichostatin A (4), an inhibitor of class I and II HDACs, suggesting an HDAC-independent repression mechanism.…”
Section: Introductionmentioning
confidence: 99%